Mesoporous silica nanoparticles prepared by different methods for biomedical applications: Comparative study. Issue 3 (22nd February 2021) - Ashour, Mohamed M.; Mabrouk, Mostafa; Soliman, Islam E.; Beherei, Hanan H.; Tohamy, Khairy M.
Abstract: In the current investigation, mesoporous silica nanoparticles were obtained by various techniques, namely sol–gel (S1), micro‐emulsion (S2) and hydrothermal synthesis (S3). The effect of those methods on the final features of the obtained mesoporous silica nanoparticles was studied. The obtained nanoparticles were investigated by TEM, BET surface area, Zetasizer, XRD and FTIR. The preparation method effect was evaluated on the drug release behaviour using doxycycline hyclate as a model drug. In addition, the degree of their compatibility against Saos‐2 cell line was also determined. The morphology and microstructure of silica nanoparticles were found to be dependent on the utilised method. Those techniques produced particles with particle sizes of 50, 30–20 and 15 nm and also surface areas of 111.04, 164 and 538.72 m 2 /g, respectively, for S1, S2 and S3. However, different preparation methods showed no remarkable changes for the physical and chemical integrities. The drug release test showed faster release from S2 compared with S1 and S3, which make them more applicable in cases require large doses for short periods. However, the release behaviour of S3 was satisfied for treatments which require long period with relatively highest release rate. The preparation method influenced the cell viability as S1 and S2 showed acceptable cell cytotoxicity compared with S3.